Temperature screening has negligible value for control of COVID‐19. (17th August 2020) - Mitra, Biswadev; Luckhoff, Carl; Mitchell, Rob D; O'Reilly, Gerard M; Smit, De Villiers; Cameron, Peter A
Abstract: Objective: To report the incidence of fever among patients who tested positive for SARS‐CoV‐2. Methods: Retrospective cohort study of patients who tested positive for SARS‐CoV‐2 at a single centre. Temperature at time of testing and on repeat testing within 24 h were collected. Results: At the time of testing, fever was detected (sensitivity) in 16 of 86 (19%; 95% confidence interval 11–28) episodes of positive tests for SARS‐CoV‐2. With repeat testing, fever was detected in 18 of 75 (24%; 95% confidence interval 15–35) episodes. Conclusions: In an Australian hospital, screening for fever lacked sensitivity for detection of patients with SARS‐CoV‐2.